EFFECT OF BODY COOLING ON FEED INTAKE AND FEED CONVERSION EFFICIENCY OF HAMPSHIRE PIGS DURING SUMMER1 (Indian Journal of Animal Production and Management, 2015)
An experiment was carried out at 30-sow Teaching Unit, College of Veterinary Science, AAU, Khanapara Campus for a period of four months (May 2014 to August 2014) to find out the effect of body cooling on the feed intake and feed conversion efficiency of Hampshire pigs during the summer seasons. Total twenty numbers of pregnant sows was taken for the experiment of second and third parity and each group comprises ten numbers of pregnant sows. Both Control(C) and Treatment (T) groups were provided same feeding standard in the farm. Sprinkling of water on the body of sows was practiced during the hotter part of the day in the treatment group. In the experiment period mean, environmental temperature, relative humidity and THI were taken into account. Results showed that Temperature ranged from 27.44 ± 0.43 to 33.76 ± 0.37 ºC, Relative humidity 71.49 ± 1.77 to 95.58 ± 0.71% and THI 78.49 ± 0.53 to 88.37 ± 0.49 respectively during the experimental period. The overall feed consumption and feed conversion efficiency (FCE) of the sows was recorded to be 32.22 ± 0.07 and 34.51 ± 0.09 kg and 5.46 ± 0.053 and 5.46 ± 0.059 for control and treatment groups respectively. Statistical analysis revealed significant difference (P
Keywords: Hampshire; sprinklers; feed intake; feed conversion efficiency